Effects of the Intestinal Status and Clinical Factors of Korean Middle-Aged People Through the Consumption of Functional Foods Containing Auricularia auricula-judae Powder: Prospective, Randomized, Open-Label, and Control Comparative Trial - Eun-ha Son; Dong Hoon Jung; Hyeri Shin; Sanghwa Lee; Youngsun Kim; Hee-sook Lim (Clinical nutrition research, 2025)
This study aimed to evaluate the effects of functional foods containing Auricularia auricula-judae powder on gut health and clinical indicators in middle-aged and older adults. Participants were randomly assigned to either the intervention group (n = 24) or control group (n = 26), and assessments including anthropometric measurements, blood analyses, and dietary intake surveys were conducted. The intervention group consumed functional foods containing A. auricula-judae powder twice daily for 8 weeks. No statistically significant differences were observed in the gut environmental parameters between the 2 groups. However, reductions in waist circumference (p < 0.021), abdominal obesity (p < 0.006), and triglyceride levels (p < 0.016) in the intervention group were statistically significant. Additionally, an analysis of nutrient intake from meals other than the intervention food revealed a significant increase in dietary fiber (p < 0.043), vitamin B1 (p < 0.027), and folic acid (p < 0.006) intake in the intervention group. Although the intervention improved the selection of body composition and blood parameters, it failed to produce significant changes in constipation outcomes or gut environmental parameters among participants with constipation. In conclusion, the consumption of A. auricula-judae powder-based functional foods resulted in limited yet meaningful improvements, specifically in reducing waist circumference and triglyceride levels.